2013
DOI: 10.4137/cmc.s10225
|View full text |Cite
|
Sign up to set email alerts
|

Unique and Varied Contributions of Traditional CVD Risk Factors: A Systematic Literature Review of CAD Risk Factors in China

Abstract: This study is the first systematic review of risk factors for stroke in China and supports the importance of current public health initiatives to manage the risk factors appropriately to reduce risk of stroke in high risk patients. Additionally, this study has been co-authored by prominent Chinese and US physicians and researchers with expertise in cardiovascular disease, neurologic disorders, epidemiology, and real world data. While there have been several systematic reviews of real world associations of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The multivariate logistic regression analysis showed that smoking was also positively correlated with CAD, and was one of the risk factors of CAD (correlation coefficient =7.036, P<0.001). Epidemiological investigation and clinical studies worldwide have also confirmed that smoking is an independent risk factor of CAD ( 11 , 17 , 18 ). The risk of CAD for smokers is 1.5- to 4-fold that of non-smokers.…”
Section: Discussionmentioning
confidence: 85%
“…The multivariate logistic regression analysis showed that smoking was also positively correlated with CAD, and was one of the risk factors of CAD (correlation coefficient =7.036, P<0.001). Epidemiological investigation and clinical studies worldwide have also confirmed that smoking is an independent risk factor of CAD ( 11 , 17 , 18 ). The risk of CAD for smokers is 1.5- to 4-fold that of non-smokers.…”
Section: Discussionmentioning
confidence: 85%
“…There were no significant differences in the levels of TC, TG, HDL-C, LDL-C and ApoAI between the two ethnic groups ( P > 0.05 for all). In contrast with developed countries, China has experienced a considerable increase in the prevalence of CAD over the past several decades [ 23 ]. Evidence of the relationship between dyslipidemia and CAD has been established worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CAD in developing countries has increased quickly in recent years due to an increasing exposure to CAD risk factors, including diabetes, hypercholesterolemia, hypertension and smoking (3,4). CAD causes >2 million fatalities each year in China (5), resulting in extensive health problems and a burden to society.…”
Section: Introductionmentioning
confidence: 99%